Retrospective Analysis on the Impact of Triptorelin on Final Height of Girls with Precocious and Early Puberty: A Single-Center, Long-Term Study - Georgia Sotiriou; Anastasios Serbis; Assimina Galli-Tsinopoulou; Athanasios Christoforidis (Children)
Background/Objectives: To evaluate the effect of triptorelin on final height of girls with precocious or early puberty, compared to the untreated group, and to investigate factors that contribute to its maximum effectiveness in terms of final height. Methods: We collected for the last two decades the data of patients evaluated in our Pediatric Endocrinology Clinic for precocious (PP) (thelarche before 8 years of age) or early puberty (EP) (thelarche before 9 years of age) during the last two decades. Our final set included 178 girls (85 with precocious and 93 with early puberty, of whom 85 received triptorelin). Final heights, measured and documented by health professionals, and the exact date of menarche were collected after telephone communication. Logistic regression analysis assessed the effect of various parameters on the response to treatment. Results: Τhe difference in mean standard deviation (ΔSDS) of final and midparental height did not show significant difference between treated and untreated girls (ΔHeight SDS (Final − Midparental): −0.20 ± 0.89 vs. −0.28 ± 0.83, p = 0.243). The results were similar when we compared the EP (−0.22 ± 0.71 vs. −0.17 ± 0.83, p = 0.778) and PP (−0.19 ± 1.04 vs. −0.39 ± 0.83, p = 0.315) subgroups. Menarche occurred earlier in the PP group compared to the EP group (10.68 ± 1.22 vs. 11.12 ± 0.90 years, p = 0.005) and in the untreated compared to the treated group (10.31 ± 0.91 vs. 11.57 ± 0.06 years, p < 0.001 for EP, 11.53 ± 0.90 vs. 9.86 ± 0.86 years, p < 0.001 for PP). Predictors of final height were height at diagnosis (positively correlated), midparental height, and bone age at diagnosis (negatively correlated). Conclusions: There was no significant difference in final height between treated and untreated girls. Triptorelin was effective in delaying the onset of menarche. Factors contributing to a better final height in treated girls were higher height at baseline, lower midparental height, and younger bone age.